Pembuatan Bioetanol Dari Limbah Tongkol Jagung Menggunakan Proses Simultaneous Sacharificatian And Fermentation (SSF) Dengan Variasi Konsentrasi Enzim Dan Waktu Fermentasi - Zul Fadly Khaira; Elvi yenie; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
One of energy source alternative that can be used as a substitute for fossil fuel-based energy, is bioethanol. Bioethanol is biochemistry fluid from fermentation process of sugars by using microorganism. The raw material of bioethanol production is very diverse, like corn cob. Corn cob can be used as raw material for bioethanol production because contain of cellulose. This study aims to make bioethanol from corn cob with delignification process and using Simultaneous Saccharification and Fermentation (SSF) method with variation of cellulase enzyme are 3%, 5%, 7%, 9%, and 11% v/v substrate and fermentation duration are 72, 96, and 120 hours. From this research were obtained the highest bioethanol concentration is 8% on the addition of cellulase enzymes 11% v/v substrate with 72 hour fermentation time.Keyword: Bioethanol, delignification, SSF